Cellular and Humoral Immune Responses and Breakthrough Infections After Two Doses of BNT162b Vaccine in Healthcare Workers (HW) 180 Days After the Second Vaccine Dose - Mangia, Alessandra; Serra, Nicola; Cocomazzi, Giovanna; Giambra, Vincenzo; Antinucci, Stefano; Maiorana, Alberto; Giuliani, Francesco; Montomoli, Emanuele; Cantaloni, Paolo; Manenti, Alessandro; Piazzolla, Valeria (Frontiers in Public Health, 2022)
Background: Immunity and clinical protection induced by mRNA vaccines against SARS-CoV-2 has been shown to decline overtime. To gather information on immunity rate and profile deemed sufficient in protecting against hospitalization, we investigated immune response to BNT162b vaccine, 180 days (d180) after the second shot in HW. Methods: 392 subjects were enrolled. All received BioN-Tech/Pfizer from February 2020 to April 2021. The vaccine-specific humoral response was quantitatively determined by testing for IgG anti-S1 domain of SARS-CoV-spike protein. Neutralizing antibody were evaluated by a micro-neutralization assay performed incubating serial 2-fold dilution of human serum samples, starting from 1:10 up to 1:5120, with an equal volume of Wuhan strain and Delta VOC viral solution and assessing presence/absence of cytopathic effect. SARS-CoV-2 spike protein-specific T-cell response was determined by a commercial interferon-gamma (IFN-ɣ) release assay. Results: Of 352 individuals analyzed, at d180, none had results below the assay’s positivity threshold. Overall, 22 naïve (8.1%) had values above the highest threshold. Among COVID-naïve, the impact of age, observed at earlier stages, disappeared at d180, while it remained significant for COVID-experienced. Following the predictive model of protection by Khoury, we transformed the neutralizing titers in IU and used a 54 IU threshold to identify subjects with 50% protective immunity. Overall, 32.78% of naïve and 91.89% of experienced (p<0.0001) showed protective neutralizing activity. While a borderline (cutoff >100 mIU/ml) and a stronger (cutoff >200 mIU/ml) T-cell response was detectable in all the 81 COVID-experienced, among 271 naïve 7 (2.58%) and 17 (6.27%) did not show borderline or strong response, respectively. Conclusions: Low IgG titers are relatively long lasting, whereas high levels are extremely rare at d180, in COVID-naïve. Only a third of naïve maintain neutralizing response. After specific stimulation, a very limited number of naïve resulted unable to produce IFN-ɣ. IFN-ɣ could be used as a surrogate testing for cellular immune responses. The results attained in a small group of subjects with breakthrough infection suggest that simultaneous neutralizing antibody titers <20, binding antibody levels/ml <200 and IFN-ɣ <1000 mIU/ml in subjects older than 58 may identify at risk groups.